Actinomycetes from Eucalyptus and their biological activities for controlling Eucalyptus leaf and shoot blight - Himaman W. (2017)
© 2016 Elsevier GmbH. In Thailand, Eucalyptus plantations rapidly expand across the country. Leaf and shoot blight caused by Cryptosporiopsis eucalypti, Cylindrocladium sp. and Teratosphaeria destructans is a serious disease in Eucalyptus plantations. In this study, a total of 477 actinomycete strains were successfully isolated from roots and rhizosphere soil of Eucalyptus. Four hundred and thirty nine isolates were classified as streptomycetes and 38 isolates were non-streptomycetes. Among these isolates, 272 (57.0%), 118 (24.7%) and 241 (50.5%) isolates were antagonistic to Cryptosporiopsis eucalypti, Cylindrocladium sp. and Teratosphaeria destructans, respectively. All isolates were tested for their abilities to produce siderophores, indole acetic acid (IAA) and solubilise phosphate. Most isolates (464, 97.3%) produced siderophores. The majority of isolates (345, 72.3%) solubilised phosphate. In addition, almost half of these isolates (237, 49.7%) produced indol e acetic acid. Strain EUSKR2S82 which showed the strongest inhibitory effect against all tested fungi with plant growth promoting ability was selected to test with Eucalyptus. This strain could colonize plant roots and increase Eucalyptus roots length. In a detached leaves bioassay, the disease severity of EUSKR2S82-inoculated Eucalyptus leaves was only 30% compared to 95% in the control treatment. The 16S rRNA gene sequence analysis revealed that the strain EUSKR2S82 was related to Streptomyces ramulosus NRRL-B 2714 T (99.44% similarity). Identification of non-streptomycete isolates using 16S rRNA gene sequences classified them into 9 genera: Actinoallomurus, Actinomadura, Amycolatopsis, Cryptosporangium, Microbispora, Micromonospora, Nocardia, Nonomuraea and Pseudonocardia. It is evident that Eucalyptus tree harbored several genera of actinomycetes. The selected isolate, EUSKR2S82 showed potential as a candidate for biocontrol agent of leaf and shoot blight of Eucalyptus and to promote growth.